2003
DOI: 10.1108/08876040310486285
|View full text |Cite
|
Sign up to set email alerts
|

Service quality and customer loyalty perspectives on two levels of retail relationships

Abstract: This study attempts to examine the impact of service quality dimensions on customer loyalty, on two levels of retail relationships: person‐to‐person (salesperson level) and person‐to‐firm (store level). A total of 1,261 surveys were administered to shoppers who were leaving a large chain departmental store in Victoria, Australia. The results showed that service quality is positively associated with customer loyalty, and that the relationship between the two is stronger at the company level, rather than at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
229
3
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(252 citation statements)
references
References 49 publications
14
229
3
6
Order By: Relevance
“…She concluded that service expressiveness value is distinct from the performance value obtained from service delivery. Consumers satisfi ed with service quality are most likely to become and remain loyal ( Wong and Sohal, 2003 ). Kaul (2005) further observes that a store having modern equipment, good and clean physical facilities and ease in transactions would be able to yield satisfaction and patronage intentions.…”
Section: Related Studiesmentioning
confidence: 99%
“…She concluded that service expressiveness value is distinct from the performance value obtained from service delivery. Consumers satisfi ed with service quality are most likely to become and remain loyal ( Wong and Sohal, 2003 ). Kaul (2005) further observes that a store having modern equipment, good and clean physical facilities and ease in transactions would be able to yield satisfaction and patronage intentions.…”
Section: Related Studiesmentioning
confidence: 99%
“…According to survey results, level of service is a factor that significantly influences consumer satisfaction in retail stores. This quality is positively associated with customer loyalty [19]. Numerous studies have attempted to shed light on the relationship between service attitude and customer satisfaction.…”
Section: Hypothesismentioning
confidence: 99%
“…Based on studies by Parasuraman et al [29], not only is service quality defined as a global judgment or attitude related to the superiority of the service, but it is also composed of five dimensions, including tangibility, reliability, responsiveness, assurance and empathy. Many studies in different industries indicate that better service quality has a positive impact on customer trust and brand loyalty [28,[31][32][33][34].…”
Section: Service Quality Brand Trust and Brand Loyaltymentioning
confidence: 99%